Pharmacokinetics and Bioequivalence of Two Combination Metformin/Glipizide Tablets under Fasting and Fed Conditions in Chinese Healthy Subjects: A Randomized, Open-Label, Crossover Study. - Lei, Yuyan; Yan, Yu; Huang, Lifeng; Li, Canxia; Liu, Wanying; Shen, Qiuxia; Wang, Caihong; Yang, Hongying; Li, Xiaohui; Zhang, Wanyu; Chen, Jing; Su, Jiankun; et al. (Journal of Clinical Pharmacy & Therapeutics, 2024)
Metformin/glipizide tablets are a compound formulation composed of metformin hydrochloride and glipizide. This study aimed to assess the pharmacokinetics and bioequivalence of two fixed-dose combination (FDC) tablets of metformin/glipizide (500 mg/2.5 mg) in healthy Chinese subjects. We conducted a single-center, open-label, randomized, two-way crossover study with a total of 48 subjects enrolled (24 in each dietary group). The test or reference formulations were given to the subjects at random at a ratio of 1 : 1, with a seven-day washout period. Blood samples, collected at prearranged intervals before and up to 24 hours after dosage, were analyzed using validated LC-MS/MS technology to ascertain plasma concentrations of metformin and glipizide. Finally, 23 subjects completed the fasting and fed studies, respectively. In both studies, the 90% confidence intervals for the geometric mean ratios (test/reference) of the C m ax , AUC0-t, and AUC0-∞ were all found to fall within the acceptable range for bioequivalence (80%–125%). The exposure of metformin/glipizide FDC tablets in vivo was not significantly affected by food. No serious adverse events were observed. In conclusion, this study demonstrated that both the test and reference metformin/glipizide tablets exhibited bioequivalence and were well tolerated under both fasting and fed conditions. This trial is registered with CTR202686.